Analysis of pacing and kinematics in 3000 m freestyle in elite level swimmers - López-Belmonte, O.; Ruiz-Navarro, J. J.; Gay, A.; Cuenca-Fernández, F.; Mujika, I.; Arellano, R. (Sports Biomechanics, 2025)
This study aimed to determine elite swimmers` pacing strategy in the 3000 m event and to analyse the associated performance variability and pacing factors. Forty-seven races were performed by 17 male and 13 female elite swimmers in a 25 m pool (20.7 ± 2.9 years; 807 ± 54 FINA points). Lap performance, clean swim velocity (CSV), water break time (WBT), water break distance (WBD), stroke rate (SR), stroke length (SL) and stroke index (SI) were analysed including and excluding the first (0-50 m) and last lap (2950-3000 m). The most common pacing strategy adopted was parabolic. Lap performance and CSV were faster in the first half of the race compared to the second half (p < 0.001). WBT, WBD, SL and SI were reduced (p < 0.05) in the second half compared to the first half of the 3000 m when including and excluding the first and last laps for both sexes. SR increased in the second half of the men`s race when the first and last laps were excluded. All studied variables showed significant variation between the two halves of the 3000 m, the highest variation being obtained in WBT and WBD, suggesting that fatigue negatively affected swimming kinematics.